2021
DOI: 10.1016/j.apmr.2021.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Disability and the COVID-19 Pandemic: A Survey of Individuals With Traumatic Brain Injury

Abstract: To identify the consequences of the coronavirus 2019 (COVID-19) pandemic for individuals with traumatic brain injury (TBI), with particular attention to unique effects for individuals with chronic disability. Design: Individuals with and without a history of TBI completed a web-based survey. Setting: Participants were recruited from the Vanderbilt Brain Injury Patient Registry in Nashville, TN, and completed the survey from their homes between May and June 2020, during social distancing related to the COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 35 publications
1
39
3
Order By: Relevance
“…In this study, participants with TBI reported less frequently than NC participants that they use some platforms involving synchronous communication (eg, Zoom and Skype), although they were more comparable in their use of FaceTime. This pattern was consistent with findings from a separate survey on the COVID-19 pandemic [ 35 ], in which individuals with a history of TBI reported that they found video chat to be less successful than face-to-face communication, and some participants stated that impoverished visual and verbal cues via video chat make it more difficult to read social signals. In this context, it is interesting to consider how asynchronous communication via social media may prove even more challenging for some individuals with TBI than synchronous video chat.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, participants with TBI reported less frequently than NC participants that they use some platforms involving synchronous communication (eg, Zoom and Skype), although they were more comparable in their use of FaceTime. This pattern was consistent with findings from a separate survey on the COVID-19 pandemic [ 35 ], in which individuals with a history of TBI reported that they found video chat to be less successful than face-to-face communication, and some participants stated that impoverished visual and verbal cues via video chat make it more difficult to read social signals. In this context, it is interesting to consider how asynchronous communication via social media may prove even more challenging for some individuals with TBI than synchronous video chat.…”
Section: Discussionsupporting
confidence: 88%
“…A recent survey [47] conducted during the ongoing COVID-19 pandemic on 47 individuals in the chronic phase of moderate–severe TBI, concluded that healthcare providers should look for ways to provide tailored education and reduce social isolation for individuals with disability. They discuss a number of direct suggestions from participant responses.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey conducted in Nashville, United States, by Morrow et al. (2021) on 47 individuals in the chronic phase of moderate‐severe TBI reported that for 51.06% of the participants, the pandemic has affected their sense of mental and physical well‐being. In our case, we analyzed 20 psychological items and only in one of them a significant increase of the level of stress was reported (Impulsivity; does things without thinking).…”
Section: Discussionmentioning
confidence: 99%